Evaluation Of Cnc Routed Surface Quality Of Beech (Fagus Sylvatica L.) With Different Milling Angles As Function Of Grain Orientation - Lungu Antonela; Gurau Lidia; Cosereanu Camelia (Bulletin of the Transilvania University of Brasov. Series II: Forestry, Wood Industry, Agricultural Food Engineering, 2023)
The paper presents an experimental investigation of the quality of CNC routed surfaces with a V-Grooving router bit (90°) on various milling angles as a function of wood grain direction on beech (Fagus sylvatica L.) wood. The quality of the machined surface was first visually assessed for the presence of raised fibre and other processing defects on the routed circles with a diameter of 180 mm using feed speeds of 3 m/min and 6 m/min respectively, and spindle speeds of 12,000, 15,000, and 18,000 rpm. The quality of the processed surfaces on the circle indicated the most unfavourable CNC routing regime accompanied by the conclusions regarding the most unfavourable angles related to the grain. Further research considered the assessment of the surface quality on straight CNC routing with angles of 0, 15, 30, 45, 60, 75, and 90° related to the wood grain direction at feed speeds of 3 and 6 m/min and spindle speed of 15,000 rpm. In this case, the characterisation of the wood surface quality was made by measuring the roughness parameters. The highest values of the roughness parameters, showing the presence of the fibres detached from the surface, were recorded for the cutting angle of 60, followed closely by 75°, then 45°, and 90° at a feed speed of 3 m/min. No significant difference was found between the Rk of the cutting angles from 0° to 45°, but it increased significantly for 60, 75, and 90°, showing frequent deeper anatomical voids on the surface.
Keywords: CNC router; surface roughness; milling angles; beech wood